Humanitarian Law Education Strategy for Military Personnel: A Study on Effective Training Programs and Their Impact on Battlefield Behavior - Arief Kurniawan Hertanto; Roy Fakhrul Rozi; Tarsisius Susilo; Antonius Adi Santoso; Taufik Zega (Journal of Social Research, 2025)
Humanitarian law education for military personnel plays a crucial role in reducing violations of international law during armed conflicts. Humanitarian law aims to protect individuals who are not or are no longer involved in combat, such as civilians and prisoners of war, as well as to limit the means in war to reduce human suffering. This study aims to explore effective strategies for humanitarian law education for military personnel, focusing on training programs implemented in several countries and their impact on soldiers' behavior on the battlefield. Through case studies of training programs in countries that have successfully integrated humanitarian law principles into military education, this research identifies successful approaches as well as challenges faced in its implementation. The findings indicate that a deeper understanding of humanitarian law can enhance military personnel's adherence to international law and reduce violations in the field. This research provides recommendations for the development of more comprehensive and sustainable training programs, integrating ethics, morality, and practical application of humanitarian law in military daily life.